Post-storm debris removal considering traffic and psychological impacts. Issue 2 (2nd January 2019) - Hu, Zhi-Hua; Sheu, Jiuh-Biing; Wei, Chen; Hu, Shao-Long
ABSTRACT: A multi-objective linear program is formulated for systematically minimizing aggregate logistics costs, including economic costs (debris transportation and sweeping, and urgent recruitment of related trucks and people), traffic impacts (blockage and congestion caused by debris removal) and psychological impacts (perceived by communities) in post-storm debris removal. Three distinctive features are formulated: the urgent recruitment prices of debris treatment resources decrease with time; the traffic impacts relate with the busy degrees of the corresponding roads, and the settings are different for nighttime and daytime; and the psychological impact is formulated as a function of waiting time. The numerical studies performed by the proposed model reveal that reducing the economic cost and reducing the psychological impact are conflicting objectives; a 90% decrease in psychological impact increases economic cost by 10%; work at nighttime can decrease traffic and psychological impacts. Some generalizations and managerial implications are also discussed based on numerical studies.